A Facile and Rapid Immobilization Method of Titanium Dioxide-Alginate Composite for The Photocatalytic Removal of Reactive Black-5 - Lam, Weng Hoong; Tee, Lee Hong; Ban, Zhen Hong (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2024)
A facile and rapid approach to immobilize nano-sized titanium dioxide (TiO2) using a renewable biopolymer (i.e. alginate) has been successfully demonstrated. TiO2 exhibits a positively charged surface in acidic environment due to the presence of hydroxyl groups. Meanwhile, alginate polymer is negatively charged at any pH due to the presence of carboxylic group in the polymer chain. The negatively charged alginate polymer and positively charged TiO2 formed composite instantaneously when the alginate polymer was introduced into the TiO2 nanoparticles suspension. The TiO2-alginate (TiO2-A) composite photocatalyst was characterized using thermogravimetric analysis (TGA), field emission-scanning electron microscopy (FE-SEM) coupled with energy dispersive X-ray (EDX) analysis and Fourier Transform Infrared (FTIR). Thermogravimetric analysis indicated that incorporating TiO2 into sodium alginate increases its decomposition temperature due to the stability of TiO2 at elevated temperatures, with the TiO2 content estimated in the composite being 55.6%, lower than the theoretical calculation of 62.8%. FTIR analysis revealed a shift in the peak of the carboxylic group of sodium alginate, suggesting composite formation through electrostatic interactions with TiO2 nanoparticles, while FESEM analysis showed that the TiO2-A composite surface exhibited more pores compared to protonated alginate. The TiO2-A composite was able to remove 90% of the Reactive Black 5 (RB5) in less than 200 min under Ultra-violet (UV) illumination. The optimal pH to remove RB5 was found to be pH 2 due strong electrostatic attraction of negatively charged RB5 on the positive surface of TiO2 nanoparticles. The photocatalyst can be recovered by simple separation method, i.e. gravitational settling, and reused for 10 consecutive cycles with efficiency greater than 90% consistently. The TiO2-A composite is a promising immobilized photocatalyst for practical application in wastewater treatment. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).